A study on peristaltic flow of micropolar fluids - Chandra, Subhash; Pandey, Sanjay Kumar (Institute of Physics Publishing, 2018)
In this paper, we presented a mathematical formulation deals with the flow of micro-polar fluid in a circular cylindrical tube of non-uniform cross-sectional area induced by peristaltic waves of increasing amplitude. This is an intended act to model the swallowing of various types of foods in the oesophagus which suffers from a hiatus hernia. Due to sliding hiatus hernia, the cross-section of the lower oesophagus does not remain uniform. The impact of bulging, which is formed by various combinations of divergence and convergence, has been examined. The effects of dilating amplitude, a slope of the tube wall, the coupling number, and micro-polar parameter, have been investigated
An application to sliding hiatus hernia
Keywords: Study on peristaltic flow; Micropolar fluids; Sliding hiatus hernia